Literatura młodzieżowa w Polsce w świetle statystyki wydawniczej (1944-2012) = Young-adult fiction in Poland in the light of publishing statistics (1944-2012) - Sadowska, Jadwiga (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article presents a statistical analysis of youth literature publications in Poland between 1944-2012. It is based on the data contained in the statistical yearbook "Ruch Wydawniczy w Liczbach". It presents the number of books, translations, first editions and reprints, with a special focus on the 1990-2012 period when the economic and legal changes occurred in the Polish publishing market. It contains rankings of the most frequently published Polish and foreign authors and most frequently published Polish and foreign books throughout the post-war period. In general it should be noted that the youth book market in Poland does not exceed a few percent of the published literature, and the average annual number of publications is about 210 books. The most popular authors belong to world classics (Verne, Twain, Montgomery, Curwood, May, Kipling) and Polish well-established authors (Niziurski, Makuszyński, Szklarski, Chmielewski, Jurgielewiczowa, Siesicka). The first editions are more popular than re-prints, and the share of translations of foreign literature is increasing, reaching 70% in some years.
Keywords: literatura młodzieżowa; statystyka; ruch wydawniczy; youth literature; statistics; publishing movement